THE FOSSIL RECORD OF PHOBEROMYS PATTERSONI MONES 1980 (MAMMALIA, RODENTIA) FROM URUMACO (LATE MIOCENE, VENEZUELA), WITH AN ANALYSIS OF ITS PHYLOGENETIC RELATIONSHIPS - Horovitz I.; Sanchez-Villagra M.R.; Martin T.; Aguilera O.A. (My University, 2006)
An almost complete skeleton of Phoberomys pattersoni is reported from the Urumaco Formation in northwestern Venezuela. Phoberomys attained the largest body size among known rodents and it lived during the Late Miocene and/or Early Pliocene of Argentina, Brazil and Venezuela. Phoberomys pattersoni is probably the second largest species within its genus. The lower molar enamel shows little difference in thickness between the trailing and leading edges in the first and second lophs, whereas in the third loph the trailing edge is much thinner than the leading edge. In the leading edge of the distal loph the enamel consists of two layers, each covering approximately 50% of the entire enamel thickness, one consisting of thick Hunter-Schreger bands inclined 15-20° towards the occlusal surface, the other formed by radial enamel with the prisms inclined towards the occlusal surface. The postcranial skeleton shows a mosaic of unusual features among caviomorphs (e.g. absence of a supratrochlear foramen) and shared conditions (e.g. tuber calcis of the calcaneum that is wider than deeper dorsoventrally) that evolved in parallel in different lineages. The phylogenetic position of Phoberomys is determined on the basis of a simultaneous analysis of molecular and morphological data of select rodents. Phoberomys appears as the sister group of the Recent genus Dinomys. Several derived character conditions are shared with Dinomys: presence of a site for attachment for the m. rectus femoris on the lateral side of the innominate in the shape of an elongated crest; trochlear ridges of the femur proximally convergent; medial condyle of the femur wider than the lateral one in posterior view; medial ridge of the astragalar trochlea reaches posteriorly further than the lateral one; proximal portion of the coronoid process extends further anteriorly than the medial (and distal) process (or anconeal process). More than one species of Phoberomys may be present in the Urumaco Formation.
Keywords: CAVIOMORPHA; HYSTRICOMORPHA; NEOEPIBLEMIDAE; DINOMYS; POSTCRANIUM; ENAMEL; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен